A revision of the New World species of Cremnops Förster (Hymenoptera: Braconidae: Agathidinae) - Tucker, Erika M.; Chapman, Eric G.; Sharkey, Michael J. (Zootaxa, 2015)
The New World species of the genus Cremnops are revised. Thirty-three species of Cremnops are treated; five are described as new, i.e., C. bertae sp. nov., C. cluttsis sp. nov., C. nymphius sp. nov., C. wileycoyotius sp. nov. and C. witkopegasus sp. nov. Six species are synonymized, i.e., Cremnops caribensis Berta, 1998, is synonymized under C. guanicanus Wolcott, 1924; C. nigrosternum (Morrison 1917) is synonymized under C. haematodes (Brullé 1846); C. punctatus Berta, 1998, is synonymized under C. marshi Berta, 1998; C. sharkei Berta, 1998, is synonymized under C. montrealensis (Morrison 1917); C. turrialbae Berta de Fernandez, 1998, is synonymized under C. ferrugineus (Cameron 1887); and C. misionensis Berta, 1987, is synonymized under C. slossonae (Morrison 1917). Cremnops florissanticola is transferred to its original combination Bracon florissanticola Cockerell, 1919, st. rev. Included are a molecular phylogeny, a dichotomous key, links to distribution maps, an electronic interactive key, and images of holotypes.